Poly(tetrafluoroethylene-co-perfluorovinyl ether sulfonamide) for anion exchange membranes. Issue 16 (8th April 2016) - Liu, Xundao; Gao, Hongrong; Chen, Xiaohong; Hu, Yong; Li, Hong; Zhang, Yongming
Abstract : A soluble perfluorinated polymer poly(tetrafluoroethylene- co -perfluorovinyl ether sulfonamide) (PFSO2 NH2 ) was successfully synthesized and used for preparation of perfluorinated anion exchange membranes with good conductivity and alkaline stability. Abstract : A soluble perfluorinated polymer poly(tetrafluoroethylene- co -perfluorovinyl ether sulfonamide) (PFSO2 NH2 ) was successfully synthesized and used for preparation of perfluorinated anion exchange membranes (AEMs). PFSO2 NH2 is soluble in many solvents and has excellent alkaline stability. The perfluorinated AEM (PFSO2 NH–MGMC–OH) which was synthesized by the reaction of PFSO2 NH2 with 4-methyl-4-glycidylmorpholin-4-ium chloride (MGMC) exhibits a hydroxide conductivity of 60.4 mS cm −1 at 80 °C and 13.8 mS cm −1 at 30 °C, respectively. The transport numbers of the membrane are 0.91 for Cl − and 0.06 for Na + . The membrane shows good alkaline stability that it maintained 80.1% hydroxide conductivity and 85.6% ion exchange capacity (IEC) values after immersion in 8 M KOH over 30 days at 60 °C. This soluble PFSO2 NH2 with high thermal and alkaline stability could be used as a precursor for other perfluorinated functional polymers and membranes.